Strategi Corporate Communication dalam Rebranding PT Semen Indonesia (Persero) Tbk - Nisrina Nur Atikah Putri; Diana Amalia (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
This research uses qualitative descriptive studies using case study studies of a company. The data collection techniques used are observation techniques, documentation interviews and literature studies. The results of this study show that there are four Corporate Communication Strategies carried out by GIS in rebranding, consisting of fact finding, planning, communicating and evaluating. The fact finding strategy is carried out to find out information and facts to later become a strategy in carrying out rebranding activities. Activities carried out in the planning strategy consist of rebranding planning, involving internal and external parties, redesign, creating brand guidelines, videos, jingles, managing official company accounts, creating social media content mapping and. media mapping. Meanwhile, the activities carried out in the communication strategy consist of socializing brand guidelines, publishing through videos and photos, replacing desktop displays, screening jingles, press releases, holding activations, coordinating with media partners, and media placement. The evaluating strategy is carried out through publication activities, socialization processes, and media monitoring. Based on the rebranding activities carried out by SIG, there are some people who still do not know about the rebranding carried out by GIS and think SIG is a new company.